Innovation Capability and Supply Chain Management: Empirical Study of Indonesian Traditional Herbal Medicine Products - Octavia, Ade; Sriayudha, Yayuk; Ali, Hapzi (International Journal of Supply Chain Management, 2020)
Abstract— In today's scenario, supply chain processes have been greatly influencing businesses and trades globally. The purpose of this research is to analyze the effects of the supply chain management on the model capabilities of innovation and competitive advantage of Indonesia traditional herbal medicine. Design research is qualitative and quantitative approaches and using data collecting technique: FGD and survey sample. The research sample was 150 people consumers of Indonesian traditional herbal medicine. The analysis tool is the Structural Equation Modeling (SEM). The results show that there is a relationship between positioning product and competitive advantage. Competitive advantage is the variable consequences of innovation capability and positioning product Indonesian traditional herbal medicine products.